É subúrbio isto aqui : urbanidade e memória dos moradores do bairro de Ponta Grossa Maceió Alagoas - Oliveira Junior, José de (2009)
The city of Maceió situated in the State of Alagoas had 25 lived spaces considered like district. In the 2000 year the number of districts in the city increases for 50. With this new configuration the lived spaces of the city started to be divided in seven administrative regions. Each town joins a group of districts of the same administrative region. In this way, Ponta Grossa is one of the most ancient of the city of Maceió that suffered and it is suffering significant alterations with the advancements of the urbanization and the way of being of the courtesy checked in the last times in the world, in the country and in the capital. Along the time lived in the residents' number of this town it is growing expressively and, with that, it appeared also to the transformations of the ancient forms of sociability. There investigated the history and identity space-partner of the district of Ponta Grossa, being the objective of this investigation to urbane construction of the Brazilian society through the urbanization of the district and the memory and history of the residents of this town of the city of Maceió.